THE EFFECTS OF ETHICAL CULTURE AND LEADERSHIP STYLE ON FRAUD PREVENTION WITH ORGANIZATIONAL COMMITMENT AS A MEDIATION VARIABLE IN THE RECTOR'S BUREAU OF UNIVERSITAS SUMATERA UTARA - Aninditya Amanda; Iskandar Muda; Keulana Erwin (PT. Radja Intercontinental Publishing, 2026)
This study examines the influence of ethical culture and leadership style on fraud prevention, and investigates the mediating role of organizational commitment in those relationships at the Rector's Office of Universitas Sumatera Utara (USU). Employing a causal-associative quantitative design, data were collected from 106 employees through purposive sampling via structured questionnaires. Data analysis utilized covariance-based Structural Equation Modeling (SEM) using IBM AMOS software. Results indicate that ethical culture has a significant positive direct effect on fraud prevention (CR = 2.589; p = 0.010), while leadership style exerts no significant direct effect (CR = 1.901; p = 0.057). Both ethical culture (CR = 2.426; p = 0.015) and leadership style (CR = 2.743; p = 0.006) significantly and positively influence organizational commitment. Organizational commitment, in turn, significantly promotes fraud prevention (CR = 3.579; p < 0.001). Sobel test results confirm that organizational commitment significantly mediates the effect of ethical culture (t = 2.008; p = 0.045) and fully mediates the effect of leadership style (t = 2.177; p = 0.029) on fraud prevention. These findings underscore the critical importance of cultivating ethical climate and building employee commitment as complementary mechanisms in institutional fraud prevention strategies.